Safety Attitude and its associated factors among workers in Micro- and Small-Scale Enterprises (MSSEs) in Shiraz - Mehdi Jahangiri; Anahita Fakherpour; Sepideh Monsef; Mohadeseh Nezam (Shiraz University of Medical Sciences, 2017)
Background: Individual factors play an important role in the safety performance of small and medium-sized enterprises that might have physical, mental or psychological nature. Some of these factors are related to the subjects' personality and unchangeable; however, others are related to motivation and attitude, which could be improved through training. This study aimed to assess the safety attitude and its effective factors among workers in micro- and small-scale enterprises (MSSEs) in Shiraz in 2015.Methods: This cross-sectional study was conducted on 349 workers in MSSEs. Safety Attitude Questionnaire (SAQ) was filled out by self-report method which consisted of questions including general information, cognitive, affective and conative ‎dimensions. Then, SPSS software version 22 was used to assess the significant difference between the variables (p-value <0.05).Results: The mean score of safety attitude was (103.05±8.73 out of 125). The minimum and maximum safety attitude scores were related to affective (16.13±3 out of 20) and cognitive (46.7±4.12 out of 55) dimensions, respectively. Also, there was a significant difference between the educational level and safety attitude. Workers with higher education had higher safety attitude scores.Conclusions: The results showed that most of the workers had safety attitude but they were not desirable in affective and conative domains. Therefore, it is required to enhance the affective domain through training the workers, enhancing their participation, paying attention to their views on occupational safety and health issues and ‎promote the conative one through the supervision of legal authorities